Fly Fishing in Connecticut : A Guide for Beginners - Murphy, Kevin (Kevin J.), 1949- (Book collections on Project MUSE., 2012)
In this book, a long-time resident and devoted fly fisherman imparts a wealth of knowledge about fly fishing in Connecticut. Kevin Murphy teaches novice anglers about the state's trout hatcheries and stocking programs, the differences between brook, brown, and rainbow trout, and offers easy-to-follow instructions on the basics of fly fishing. In this concise text, the reader finds the essentials in fly fishing gear, stream tactics, casting, and a host of related topics. In addition, would-be anglers gain a useful glimpse into the history of fishing in the state, plus important tips on stream c.